Development in Soil Chronosequence Research from 1994 to 2024: A Bibliometric Analysis Using CiteSpace - Jingtao Wu; Wenyan Yang; Manman Fan; Huan Zhang; Zhengwei Ye; Muhammad Shaukat (Agriculture)
Soil chronosequences are crucial for understanding pedogenesis and ecosystem dynamics, yet a systematic bibliometric analysis of this field remains absent. To investigate hotspots and trends, this study used CiteSpace to analyze 4075 publications from the Web of Science Core Collection (1994–2024). The results revealed a steady increase in publications over time, led by the USA (1287 articles) and China (1093 articles). Wardle David A. emerged as the most influential researcher (67,519 citations) for his contributions regarding microbial-driven pedogenic feedbacks. The Chinese Academy of Sciences was the top institution, contributing 13.3% of articles and achieving the highest centrality of 0.21. Geoderma (IF = 5.6) was the most cited journal (2258 citations), with key contributors including Vitousek (530 citations) and Walker (415 citations) from the USA and Wardle (411 citations) from Sweden. Research hotspots in this field were nutrient cycling, vegetation succession/ecological restoration, and soil microbial community dynamics. Three thematic shifts were identified: early focus on conceptual frameworks, expansion to ecological restoration and carbon dynamics, and recent diversification into microbial communities, coastal ecosystems (e.g., mangroves, Spartina alterniflora), and anthropogenic impacts (e.g., heavy metals). The research has evolved significantly from 1994 to 2024, with a growing emphasis on interdisciplinary approaches and practical applications. This analysis provides a comprehensive synthesis of soil chronosequence research, advancing our understanding of pedogenesis and informing sustainable land-management strategies.